THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING WRITING TEXT FOR TENTH GRADE AT SMA YAYASAN PENDIDIKAN MULIA - Nurvita Sari Silalahi; Masitowarni Siregar (Universitas Negeri Medan, 2021)
THE IMPLEMENTATION OF GENRE-BASED APPROACH INTEACHING WRITING TEXT FOR TENTH GRADE AT SMA YAYASANPENDIDIKAN MULIA*Nurvita Sari Musdiani Silalahi**Dr. Masitowarni Siregar, M.Ed.ABSTRACTNurvita Sari Musdiani Silalahi, 2021. Registration Number: 2163321037. TheImplementation of Genre-Based Approach in Teaching Writing Text forTenth Grade at SMA Yayasan Pendidikan Mulia. A Thesis. English andLiterature Department. Faculty Languages and Arts. State University ofMedan, 2021.The objectives of this study were to discover the implementation of Genre-BasedApproach in teaching writing text for Tenth Grade at SMA Yayasan PendidikanMulia and to investigate the reasons why teachers use Genre-Based Approach.This study was conducted by using descriptive qualitative design. The subject ofthis study was English teacher and students in grade tenth from SMA PendidikanMulia. The techniques of collecting data were observation, interview, anddocumentation. The data were taken from SMA Swasta Mulia Medan, from theresearch, it was found that in applying Genre-Based Approach in Englishcurriculum, and there are five steps that teacher implemented: building knowledgeof field, modeling, joint construction, independent construction and linking relatedtext. From the teacher‟s interview, the result could be found that the reasons whythe teacher of SMA Swasta Mulia Medan using Genre-Based Approach and theproblem faced by teacher and also the solution in teaching writing text.Keywords: Genre-Based Approach, Descriptive Text, Writing Skill.